Moral development : theory and applications - Vozzola, Elizabeth C.; Senland, Amie K. (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Moral Development offers a comprehensive overview of classic and current theories of moral development and applications of these theories in various counseling and educational settings. It examines changes across time and experience in how people understand right and wrong, and individual differences in moral judgements, emotions, and actions. Elizabeth C. Vozzola and Amie K. Senland review the latest research in the field and integrate classic work with contemporary perspectives on assessment and treatment. Part 1 provides an understanding of a range of theories, explaining their strengths and challenges, and offering examples of how these theories apply to helping professionals. It covers Freud, Piaget, Kohlberg, Rest, Gilligan, Nodding, Bandura, Turiel, Nucci, Narvaez, Haidt, and Shweder. Part 2 highlights promising applications of moral development theory in education and counselling. Fully updated with new chapters on faith development and moral and prosocial development in infancy and early childhood, the text explores specific approaches to helping clients with a variety of clinical or developmental challenges and provides an excellent resource for courses addressing the CACREP program objectives for Human Growth and Development. It also integrates issues of gender, ethnicity, and culture throughout to prepare readers for practicing in a global culture and presents a new perspective: the cultural developmental approach. Illustrated throughout with examples that highlight applications of moral development concepts in today's media, it also includes interviews from some of today's leading theorists and practitioners. Ideal as a text for advanced courses on moral development and moral psychology, as well as courses on human, child, social and personality development taught in psychology, counselling, education, human development, family studies, social work, and religion. Its applied approach also appeals to mental health and school counsellors"--
Keywords: Moral development; PSYCHOLOGY / Developmental / Child; EDUCATION / Educational Psychology; RELIGION / Ethics